College sport and declining stadium attendance : designing adaptive strategies - Abeza, Gashaw (SAGE Business Cases., 2018)
This case study presents the challenge of declining football attendance that a number of NCAA football programs are facing. The case participants (as members of a hypothetically formed advisory board) are asked to develop adaptive strategies and tactics to respond to this challenge by conducting an in-depth examination of fans' declining stadium attendance and proposing recommendations to the Pac-12 Commissioner's office. Particularly, students are expected to detail the reasons for fans' declining stadium attendance, to identify the short-term and long-term implications of declining stadium attendance, and to specify adaptive (corrective) strategies that can be designed based on Arizona State University's ticket-related marketing initiatives as a template. As a member of the advisory board, students are asked to address a list of questions and provide recommendations to address the challenge.